Flipped Learning During a Global Pandemic: Empowering Students with Choice (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
The purpose of this paper is to provide a research brief on current studies related to utilizing a flipped learning model. The flipped model entails students engaging with a recorded lecture prior to live class time, allowing for more student engagement with content, classmates, and the instructor during class time. A flipped model empowers students with more choice and control over their learning, can improve student achievement, and can reduce student anxiety. During a global pandemic when nearly all higher education institutions have rapidly transitioned to online learning platforms, a flipped model can provide a blended, balanced approach to student learning.